Process Validation of Highly Potent Antidiabetic Tablets of Voglibose 0.2 Mg - Tijare, Lokesh K.; Deshmukh, Lokesh T.; Mohod, Abhinay A.; Bhandakkar, Vivek M.; Hore, Santosh; Padole, Nitin N. (Asian Journal of Pharmaceutical Research and Development, 2022)
Diabetes mellitus is chronic disorder which affecting number of persons worldwide, alpha glycoside inhibitors like Voglibose is a highly potent and tolerant alpha glycoside inhibitor as compare to other diabetic drugs, the main objective of this process validation is to provide documentary evidence that the manufacturing process of Voglibose Tablet IP 0.2 mg will consistently and reproducibly produce a product, which meets predetermined specifications and quality attributes. The critical process parameter was identified with the help of process capability and evaluated by challenging as per in-house specification. Three initial process validation batches (T17L004, T18L003, T19A013) of same size, method, equipment & validation criteria were taken. As per the process validation protocol critical parameter identified like sifting, dry mixing, wet granulation, drying, sifting and milling, blending &lubrication, compression at different stages and blister packing and evaluated as per process validation protocol. Conclusion: Based on evaluation of manufacturing process and analytical data it is concluded that the employed manufacturing process for Voglibose Tablet IP 0.2 mg shall be consistently& reproducibly produce a product which meeting its predetermined specification and quality attributes, hence it is considered to be validated.